The effects of prediction representations on implicit learning: Evidence from sentence reading and perceptual identification - Xuliu Ren; Xin Xin; Xiaorong Gao; Guiqin Ren (Heliyon, 2024)
Predicting errors can facilitate implicit learning, but the long-term consequences of prediction errors are not yet fully understood. Especially when predictions are disconfirmed, it remains unclear whether initially correct prediction representations persist or are suppressed. In this study, participants first engaged in a sentence reading task and then performed a perceptual identification task after completing an N-back task or after a 24-h delay. The perceptual identification task presented previously expected and unexpected words and previously predicted but not presented words to measure implicit memory for the critical items. This study aims to investigate the mechanisms underlying the persistence of prediction representations and the long-term effects of prediction errors on implicit learning. Our results indicate that prediction errors can promote implicit learning and can persist for more than 24 h. Furthermore, originally correct but not seen in reality prediction representations persist to facilitate performance on the implicit memory task after 24 h. This may reflect long-term changes in the internal representation probabilities of prediction representations.